An ultrasonication-aided self-assembly strategy toward a PTCDA/RGO film cathode for organic K-ion full batteries. Issue 60 (6th July 2022) - Xu, Yali; Wang, Haozhi; Shen, Yuping; Yang, Chao; Chen, Xiaohua; Fan, Binbin
Abstract : A PTCDA/RGO-50% film with π–π interaction between PTCDA and RGO was designed to alleviate the solubility of PTCDA, and demonstrates excellent cycling stability for K-ion batteries. Abstract : A free-standing PTCDA/RGO film was synthesized by an ultrasonication-aided self-assembly strategy to alleviate the solubility of PTCDA in organic electrolytes. The PTCDA/RGO-50% film cathode exhibits a high capacity of 135.1 mA h g −1 at 0.05 A g −1 and excellent cycling stability (capacity retention of 85% after 200 cycles) for potassium ion batteries.